PENGEMBANGAN LKS FISIKA BERORIENTASI SCIENTIFIC INVESTIGATION UNTUK MENINGKATKAN KEMAMPUAN IDENTIFIKASI VARIABEL DAN INTERPRETASI DATA MATERI FLUIDA UNTUK SISWA SMA KELAS XI DEVELOPMENT OF SCIENTIFIC INVESTIGATION-BASED WORKSHEET FOR ELEVENTH GRADE STUDENTS TO ENHANCE THE SKILLS OF IDENTIFYING VARIABLES AND INTERPRETING DATA OF THE SUBJECT FLUID - AFIFAH KHAERUNNISA PURNAMA AFIFAH KHAERUNNISA PURNAMA; BAMBANG RUWANTO BAMBANG RUWANTO (Jurnal Pendidikan Fisika, 2016)
Abstrak Penelitian ini bertujuan untuk menghasilkan produk LKS berorientasi scientific investigation yang layak digunakan dalam pembelajaran fisika bagi siswa SMA kelas XI dan untuk mengetahui hasil ketercapaian siswa dalam meningkatkan kemampuan mengidentifikasi variabel dan interpretasi data setelah menggunakan LKS scientific investigation dalam pembelajaran fisika materi fluida statik. Penelitian ini merupakan penelitian pengembangan 4-D Models (define, design, develop, dan disseminate). Produk LKS yang dikembangkan diujicoba sebanyak dua kali di SMAN 1 Ngaglik dengan 15 siswa pada uji coba terbatas dan 31 siswa pada uji coba lapangan operasional. Hasil penelitian menunjukkan bahwa: (1) Telah dihasilkan LKS berorientasi scientific investigation yang layak digunakan dalam pembelajaran fisika materi fluida statik bagi siswa SMA kelas XI yang ditinjau dari hasil telaah instrumen LKS oleh validator ahli dan validator praktisi dengan kategori sangat baik, analisis penilaian angket respon siswa dengan kategori sangat baik, serta reliabilitas ICC dengan koefisien alpha sebesar 0.785 (acceptable). 2) Persentase ketercapaian siswa dalam mengidentifikasi variabel secara keseluruhan meningkat dari 8.82% menjadi 73.76%, sedangkan kemampuan siswa dalam menginterpretasi data meningkat dari 26.98% menjadi 75.13%. Dengan demikian, LKS scientific investigation keterpakaiannya dapat dikategorikan baik. Kata kunci: lembar kerja siswa, identifikasi variabel, interpretasi data, hasil belajar Abstract This research aims to produce a scientific investigation-based student worksheet suitable for eleventh grade students to learn physics, and to measure students’ achievement level in enhancing their ability to identify variables and to interpret data after their use of scientific investigation-based in studying physics, particularly static fluids. The research is development research of 4-D Models (define, design, develop, and disseminate). The developed worksheet was use in SMAN 1 Ngaglik that involved as many as two times of trials with 15 students in limited trial and 31 students in extensive trial. The result of this research showed that : 1) a scientific investigation-based worksheet has been produced, suitable for students of eleventh grade to study physics, particularly on the subject of static fluids, as reviewed from the result of the research over the worksheet’s instrument by experts and validators, which was categorized as very good; as well as from the assessment analysis of the students’ responses, which was also categorized as very good. According to the result of ICC reliability test, an alpha coefficient of 0.785 (accepatable) has been obtained. 2) The percentage of the students’ achievement in identifying variables has overall increased, from 8.82% to 73.76%. Meanwhile the percentage of the students’ ability to interpret data has increased as well, from 26.98% to 75.14%. Therefore, the usage of this scientific investigation-based worksheet can be categorized into decent. Keywords: student worksheet, variable identification, data interpretation, learning result